2015
DOI: 10.1515/intox-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of miR-9 and miR-143 expression in urine specimens of sulfur mustard exposed patients

Abstract: Sulfur mustard (SM) or mustard gas is a chemical alkylating agent that causes blisters in the skin (blister gas), burns the eyes and causes lung injury. Some major cellular pathways are involved in the damage caused by mustard gas such as NF-κb signaling, TGF-β signaling, WNT pathway, inflammation, DNA repair and apoptosis. MicroRNAs are non-coding small RNAs (19–25 nucleotides) that are involved in the regulation of gene expression and are found in two forms, extracellular and intracellular. Changes in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…miRNAs, the important genetic regulatory factors in humans, have been reported to exert regulatory effects on the occurrence and development of liver carcinoma ( 13 ). Nevertheless, the mechanism of miR-143 involved in the development of liver carcinoma remains to be determined ( 14 ). Thus, in this study, we preliminarily investigated the mechanism how miR-143 affects the development of liver carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs, the important genetic regulatory factors in humans, have been reported to exert regulatory effects on the occurrence and development of liver carcinoma ( 13 ). Nevertheless, the mechanism of miR-143 involved in the development of liver carcinoma remains to be determined ( 14 ). Thus, in this study, we preliminarily investigated the mechanism how miR-143 affects the development of liver carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA higher expression result in abnormal proliferation and migration of tumor cells ( 12 ). Extensive studies on miRNAs revealed that the expression levels of miR-143 in many tumor cells were significantly lower than normal tissues ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, it has been reported in the sulfur mustard-resistant HaCaT human keratinocyte line (109) that changes of miRNA profile are pivotal for sulfur mustard-resistance (110) and that some of them are also critical for resistance to alkylating agent cisplatin (111). Another study addressing miRNA-9 and miRNA-143 in the urine of 32 sulfur mustard-injured patients and 32 healthy individuals reported their significant reduced excretion correlated with the ongoing post-exposure pathogenicity (112). These two miRNAs have been assigned to the regulation of central signalling pathways (MAPK, TGF-, Wnt, etc) and their down-regulation specifically associated with the reduction of the inflammation suppressing factor TGF-, thus conferring mechanistic support to the inflammatory response of mustard-induced pathology.…”
Section: Epigenetics In the Management Of Long-term Toxicity Of Vesicmentioning
confidence: 72%